Historical Statistics on Prisoners in State and Federal institutions, Yearend 1925-1986: (United States) ([Verlag nicht ermittelbar], 1989)
This data collection supplies annual data on the size of the prison population and the size of the general population in the United States for the period 1925 to 1986. These yearend counts include tabulations for prisons in each of the 50 states and the District of Columbia, as well as the federal prisons, and are intended to provide a measure of the overall size of the prison population. The figures were provided from a voluntary reporting program in which each state, the District of Columbia, and the Federal Bureau of Prisons reported summary statistics as part of the statistical information on prison populations in the United States.